2020
DOI: 10.1007/s42773-020-00065-z
|View full text |Cite
|
Sign up to set email alerts
|

Biochar and its importance on nutrient dynamics in soil and plant

Abstract: Biochar, an environmentally friendly soil conditioner, is produced using several thermochemical processes. It has unique characteristics like high surface area, porosity, and surface charges. This paper reviews the fertilizer value of biochar, and its effects on soil properties, and nutrient use efficiency of crops. Biochar serves as an important source of plant nutrients, especially nitrogen in biochar produced from manures and wastes at low temperature (≤ 400 °C). The phosphorus, potassium, and other nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
164
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(185 citation statements)
references
References 277 publications
(284 reference statements)
14
164
1
6
Order By: Relevance
“…Chinese cabbage has a high requirement for K (Berek et al 2018;van Averbeke et al 2007) and it was determined that at harvest, the control plants had insufficient K concentrations (Jones et al 1991). The outlier of higher soil K in the 0-10 cm for the SBC than the control, in the Oxisol, could not be explained by plant response, and is another example of inconsistent K to biochar (Hossain et al 2020).…”
Section: Impact Of Biochar and Compost On Soil And Plantsmentioning
confidence: 83%
“…Chinese cabbage has a high requirement for K (Berek et al 2018;van Averbeke et al 2007) and it was determined that at harvest, the control plants had insufficient K concentrations (Jones et al 1991). The outlier of higher soil K in the 0-10 cm for the SBC than the control, in the Oxisol, could not be explained by plant response, and is another example of inconsistent K to biochar (Hossain et al 2020).…”
Section: Impact Of Biochar and Compost On Soil And Plantsmentioning
confidence: 83%
“…The findings of this study indicated that B1 supplementation increases the Mg content. The increased availability of Ca and Mg in the soil promotes crop production [ 18 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to overcome the problem consist in collecting rainwater from greenhouses or applying some technologies to improve the quality of the available water [6]. Other solutions may come from different approaches; for example, the use of zeolite, expanded clay or biochar as substrates contributes to the removal of Na + thanks to their cation exchange capacity, increasing the availability of Ca 2+ and Mg 2+ in substitution of sodium [11,12]. The use of properly treated wastewater, both from soilless and municipal wastewater, can contribute to save freshwater [13,14].…”
Section: Advantages and Limits Of Soilless Agriculture In The Process Towards Sustainabilitymentioning
confidence: 99%
“…In this context, one significant point is that the processing costs can be externalized (held by the energy producer) instead of being charged by the growing media manufacturer [17]. Biochar is a source of organic matter, nitrogen and other nutrients that can be beneficial for use as growing substrate [12,[18][19][20]. The initial nutrient content and its rate of release into the nutrient solution should be computed in the final nutrient supply count.…”
Section: Advantages and Limits Of Soilless Agriculture In The Process Towards Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation